2021
DOI: 10.3390/agronomy11040625
|View full text |Cite
|
Sign up to set email alerts
|

Cactus Pear as Roughage Source Feeding Confined Lambs: Performance, Carcass Characteristics, and Economic Analysis

Abstract: The effect of diets containing 0% of wheat bran levels (control buffel grass and cactus pear) contrasted with diets with cactus pear as the only forage source and wheat bran levels (30; 37 and 44%) on nutrient digestibility, feed intake, animal performance, carcass characteristics, and economic analysis was evaluated. Twenty-eight male, non-castrated crossbred lambs (22.6 ± 2.37 kg) were submitted to confinement for 62 days. A completely randomized design was used with four treatments and seven repetitions. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
0
0
Order By: Relevance
“…However, ADG observed in this study (216.7 -219.1 g/day) were lower than that reported by Suliman et al (2021) (310 g/day) but higher than that of Shaker et al (2002) (207 g/day), and Jawasreh et al (2019) (180 g/day) for the same breed. Slaughter weight (42.7 -44.5 kg), hot carcass weight (19.7 -20.7 kg), and cold carcass weight (19.1 -20.1 kg) varied considerably, whereas, cold carcass yield (44.5 -46.6 %) and chilling loss (2.2 -3.1 %) were corroborated by earlier studies (Greer and Jones 1997;Carrasco et al 2009;Suliman et al 2021;Silva et al 2021;Atsbha et al 2021). Ramírez-Retamal et al (2013) found that carcasses with smaller D values but more F value showed the highest compactness which is in line with the results of earlier studies (Carrasco et al 2009;Diaz et al 2002).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, ADG observed in this study (216.7 -219.1 g/day) were lower than that reported by Suliman et al (2021) (310 g/day) but higher than that of Shaker et al (2002) (207 g/day), and Jawasreh et al (2019) (180 g/day) for the same breed. Slaughter weight (42.7 -44.5 kg), hot carcass weight (19.7 -20.7 kg), and cold carcass weight (19.1 -20.1 kg) varied considerably, whereas, cold carcass yield (44.5 -46.6 %) and chilling loss (2.2 -3.1 %) were corroborated by earlier studies (Greer and Jones 1997;Carrasco et al 2009;Suliman et al 2021;Silva et al 2021;Atsbha et al 2021). Ramírez-Retamal et al (2013) found that carcasses with smaller D values but more F value showed the highest compactness which is in line with the results of earlier studies (Carrasco et al 2009;Diaz et al 2002).…”
Section: Discussionsupporting
confidence: 79%
“…However, its use is limited by drastic variation in chemical composition, such as dry matter (3.7 -94%), crude protein (3.3 -11.6%), crude fiber (8.5 -34%), and in vitro digestibility (66.7 -90%). These drastic variations may result in non-pathological diarrhoea, bloat, and weight loss when cactus is used as the only source of fiber in small ruminant feeding (Tegegne et al 2007;Maciel et al 2018;Silva et al 2021). Therefore, it is used in combination with different types of feedstuffs to reduce these unwanted outcomes, such as Tifton 85 hay (Vieira et al 2008), soybean hulls (Souza et al 2009), whole cotton seed (Costa et al 2012), sugarcane bagasse (Pessoa et al 2013), Maniçoba hay and silage (Maciel et al 2018), and wheat bran as energy concentrate (Silva et al 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, however, the cactus diets, particularly the 10% inclusion level, tended to reduce inclusion costs of these ingredients and increased the average gain/return during drought scenario. The same was true in the study by De Waal et al [38] and Balduíno da Silva et al [39], where sheep fed diets containing spineless cactus attained higher economic returns/body gains than non-cactus diets. The trend changed for the drought scenario where a 20% cactus inclusion level resulted in lower average gain/return.…”
Section: Economic Implications Of Spineless Cactus Inclusion In Cattl...supporting
confidence: 73%
“…The association of a spineless cactus to buffel grass, pornunça and gliricidia in the composition of mixed silages reduces the levels of NDFap and ADF that these plants present in their composition; therefore, the reduction in fibrous fractions contributed to the rapid ruminal emptying, since the spineless cactus does not have enough fiber to limit consumption through physical filling [43], which favored the obtained results. In this sense, we can infer that the supplementation of these forage plants can provide small ruminants with a silage of high nutritional value.…”
Section: Intake Digestibility and Weight Gainmentioning
confidence: 78%